Increased Expression of Zyxin and Its Potential Function in Androgenetic Alopecia - Liu, Qingmei; Shi, Xiangguang; Zhang, Yue; Huang, Yan; Yang, Kai; Tang, Yulong; Ma, Yanyun; Zhang, Yuting; Wang, Ji'an; Zhang, Li; Zhang, Qi; Liu, Xiao; et al. (Frontiers in Cell and Developmental Biology, 2021)
Androgenetic alopecia (AGA) is the most common progressive form of hair loss, occurring in more than half of men aged > 50 years. Hair follicle (HF) miniaturization is the feature of AGA and dermal papillae (DP) play key roles in hair growth and regeneration by regulating follicular cell activity. Previous studies revealed that adhesion signal was an important factor in AGA development. As an actin-interacting protein, Zyxin (ZYX) is essential for cell adhesion and migration. Therefore, the aim of this research is to investigate the expression and potential role of ZYX in AGA. We observed that ZYX expression was elevated in AGA patients’ affected frontal HF compared to the unaffected occipital HF by real-time PCR. Moreover, increased Zyxin expression was also seen within the DP using the immunofluorescence staining. Our in vivo results revealed that ZYX knockout mice showed enhanced hair growth and anagen entry compared with the wild type mice. Within the ex vivo cultured HFs, we found that reduced ZYX expression by siRNA enhanced the hair shaft production, delayed hair follicle catagen entry, increased the proliferation of dermal papilla cell (DPC) and expression of stem cell related proteins. These results were further validated in the cultured DPCs in vitro. To further reveal the mechanism that how ZYX contributes to AGA, RNA-seq analysis was carried out to find the distinct gene signatures upon ZYX siRNA treatment in cultured hair follicle. Multiple pathways, including focal adhesion and HIF-1 signaling pathways, were found to be involved. Collectively, we discovered the elevated expression of ZYX in AGA patients’ affected frontal hair follicle and revealed the effects of ZYX downregulation on in vivo mouse, ex vivo hair follicle and in vitro DPC. These data suggested ZYX might play important roles in the pathogenesis of AGA and stem cell properties of DPC, and might be a potential therapeutic target in AGA.